2012
DOI: 10.15288/jsad.2012.73.185
|View full text |Cite
|
Sign up to set email alerts
|

Twin Study of the Relationship Between Adolescent Attention-Deficit/Hyperactivity Disorder and Adult Alcohol Dependence

Abstract: ABSTRACT. Objective: Adolescent problem behaviors such as conduct disorder and attention-defi cit/hyperactivity disorder (ADHD) are often associated with alcohol problems in adulthood, particularly alcohol dependence. This association is partly a result of shared genetic liability. However, it is unclear whether ADHD, or an ADHD subtype, shares genetic infl uences with alcohol dependence beyond those also shared by conduct disorder. Method: We evaluated phenotypic associations between adolescent conduct disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 35 publications
7
65
0
Order By: Relevance
“…36 Another theory proposes a common genetic factor underlying both ADHD and risk of SUDs, although more studies are needed to further evaluate this association. 37,38 Children and adolescents with ADHD have higher rates of grade retention and school dropout than those without ADHD. 39,40 These academic failures may increase an individual' s likelihood to use drugs as a means to escape anxiety about school.…”
Section: Exploring the Biological And Environmental Basis Of The Relamentioning
confidence: 99%
“…36 Another theory proposes a common genetic factor underlying both ADHD and risk of SUDs, although more studies are needed to further evaluate this association. 37,38 Children and adolescents with ADHD have higher rates of grade retention and school dropout than those without ADHD. 39,40 These academic failures may increase an individual' s likelihood to use drugs as a means to escape anxiety about school.…”
Section: Exploring the Biological And Environmental Basis Of The Relamentioning
confidence: 99%
“…The fact that some previous studies have used broad definitions of SUD (4-7), while others have explored the relationship between ADHD and specific SUD subtypes (such as psychoactive drug abuse, alcohol use disorder and nicotine dependence) (8)(9)(10)(11)(12)(13) makes comparisons across studies difficult. Furthermore, since SUD, and particularly alcohol use disorder, is rare in childhood but increasing in prevalence with age through adolescence and into adulthood, short follow-up time is a serious limitation of many previous studies looking at the association between ADHD and SUD (4, 9).…”
Section: Introductionmentioning
confidence: 99%
“…Some genetically informed studies suggest shared genetic risk factors for ADHD and SUD (11,15,16), while other family-based studies indicate independent transmission of SUD and ADHD, or alternatively, the presence of an etiologically distinct ADHD plus SUD syndrome (7,9,12). Clearly, additional research is needed to resolve the conflicting results of previous research.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research regarding the role of the ADHD subtypes in comorbidities with SUD is conflicting. Some authors find an association mainly between the HI subtype with SUD (76,79,80); others identified more SUD in the combined (CO) subtype (81). The IN subtype has mainly been associated with increased nicotine dependence (82)(83)(84)(85).…”
Section: Comorbiditymentioning
confidence: 99%
“…Research regarding the overlap between ADHD and comorbid conditions initially also focused on children, identifying common genetic factors for externalizing disorders (79,(117)(118)(119), with autism spectrum disorder (ASD) (120), cognitive performance such as reading problems (121), as well as with psychiatric disorders such as mood disorder (122). More recently, common genetic factors have been identified in adults for a wide range of psychiatric disorders, indicating involvement of a set of pleiotropic genes (123).…”
Section: Quantitative Genetic Studies In Adhd and Its Comorbiditiesmentioning
confidence: 99%